Peran Pemuda dalam Proses Penyusunan Rencana Pembangunan Jangka Menengah Kalurahan (RPJMKal) Wedomartani Tahun 2021-2026 - Paramitha, Dyah Pradjna; Fajarwati, Alia (P4W IPB, 2025)
Regional development planning in Indonesia is conducted at all levels, including national, provincial, district/city, sub-district, and village. One form of village development planning is the Village or Kalurahan Medium-Term Development Plan (RPJMDes/RPJMKal). The preparation of the plan must involve all elements of society, including youth. This study aims to 1) identify the role of youth in the preparation process of the Wedomartani Village Medium-Term Development Plan (RPJMKal) for 2021-2026; 2) analyze the level of participation; and 3) identify youth representatives' perceptions of factors influencing youth roles. The research was conducted using a mixed method approach with descriptive analysis. Sampling was conducted using purposive sampling method. Data were collected through interviews, questionnaires, and document analysis. The results showed that the role of youth is as a dynamizer, catalyst, motivator, innovator, and evaluator. Youth participation in the RPJMKal preparation process has reached the highest level or community power in the form of partnership. Based on the perception of youth representatives, the internal factor that influences the role of youth in the process of preparing the Wedomartani RPJMKal 2021-2026 is the age of youth. External factors that influence the role of youth include the village government, and community leaders.